2011
DOI: 10.1108/02652321111177803
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of digitally instigated insurance relationships

Abstract: PurposeThe purpose of this paper is to develop a conceptual model for explaining insurance customers' intentions towards using the internet as a channel for communication and interaction with insurance companies by integrating Technology Acceptance Model (TAM) and trust.Design/methodology/approachThe paper seeks to conceptually develop an integrated framework for studying and measuring the perceptions of customers towards using the internet as a source of communication and interaction. The TAM model is taken a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Understanding these relationships and their link to performance requires an exploratory approach which gets as close as possible to the actors involved. Bigné and Blesa (2003) also supported the importance that trust has in distributors' satisfaction with the relationship developed with manufacturers (in this case, it would be with insurers) (see also Gidhagen and Persson, 2011;Das, 2016) The present study is even more relevant if we consider the implementation of Solvency II[1], namely, because insurers are concerned that some dimensions within Solvency II will produce unintended consequence and harm both insurers and their policyholders (Insurance Europe, 2017). In addition, the regulatory system in the insurance sector presents idiosyncrasies per country (see Brophy, 2012) but it can be expected that Solvency II will cause great impact.…”
supporting
confidence: 58%
See 1 more Smart Citation
“…Understanding these relationships and their link to performance requires an exploratory approach which gets as close as possible to the actors involved. Bigné and Blesa (2003) also supported the importance that trust has in distributors' satisfaction with the relationship developed with manufacturers (in this case, it would be with insurers) (see also Gidhagen and Persson, 2011;Das, 2016) The present study is even more relevant if we consider the implementation of Solvency II[1], namely, because insurers are concerned that some dimensions within Solvency II will produce unintended consequence and harm both insurers and their policyholders (Insurance Europe, 2017). In addition, the regulatory system in the insurance sector presents idiosyncrasies per country (see Brophy, 2012) but it can be expected that Solvency II will cause great impact.…”
supporting
confidence: 58%
“…For example, insurers and intermediaries should exchange more information about customer preferences or products with more coverage, and associated services (such as an online service platform or account manager, in line with Robson et al, 2016) should be presented to customers who buy more expensive products. This recommendation is consistent with Gidhagen and Persson (2011), Huckstep (2016) and Dalla Pozza et al (2017. In this way, it would be possible to prevent customers from comparing products with low prices (in line with Gázquez-Abad and Sánchez-Pérez, 2009) and increase the attractiveness of products.…”
Section: Discussionmentioning
confidence: 54%
“…TAM was adapted to study how financial incentives could affect consumers’ intention to adopt NFC mobile payment (see Figure 1). TAM is one of the powerful models in examining the determinants of consumers’ intention to adopt new technology (Gidhagen and Persson, 2011; Kesharwani and Bisht, 2012; Kim and Shin, 2015; Koksal, 2016; Mohammadi, 2015; Patel and Patel, 2018). According to TAM, consumers’ intention to adopt a newly developed technology is determined by two beliefs: perceived ease of use and perceived usefulness (Davis, 1989).…”
Section: Review Of Literaturementioning
confidence: 99%
“…However, unlike carriers of home insurance, auto insurance, and especially life insurance policies, carriers of medical insurance may have cause to want to utilize services and interact with their providers. Research has found that other insurance carriers rarely interact with their providers and prefer to not fully utilize the product (Gidhagen and Persson, 2011). In contrast, customers who carry health insurance have the opportunity to enhance their lives by utilizing preventive services through insurance coverage.…”
Section: Enabling Factorsmentioning
confidence: 99%